Smoking and the New York State Journal of Medicine: a brief introduction - Alan Blum (Social Medicine Publication Group, 2024)
2010 marks the 25th anniversary of the publication by the New York State Journal of Medicine of the second of two theme issues on the world tobacco pandemic, the first comprehensive examination of the subject ever published by a medical journal. Aiming to challenge the medical profession to become actively involved in fighting smoking, the issues went beyond a discussion of the well known health consequences of tobacco to a consideration of the social, political, economic, agricultural, religious, and legal aspects of this growing problem.